3D detailed modeling of reinforced concrete frames considering accumulated damage during static cyclic and dynamic analysis – New validation case studies - Mourlas, Christos; Markou, George; Papadrakakis, Manolis (My University, 2019)
The study of the hysteretic behavior of reinforced concrete members that undergo static cyclic and dynamic loading conditions in cases where the loading level is close to their carrying capacity, is a challenging open research subject, which currently is being investigated by many researchers. The development of an objective and robust 3D constitutive modeling approach that will be able to account for the accumulated material damage and stiffness deterioration is of great importance in order to realistically describe the physical failure mechanisms thus numerically study the seismic performance of RC structures. The adopted concrete material model in this research work is based on the material model proposed by Markou and Papadrakakis, which was an extension of the Kotsovos and Pavlovic work. Furthermore, the use of two newly proposed damage factors that are computed through the use of the number of opening and closing of cracks during the nonlinear cyclic analysis, are further investigated and their ability in capturing the accumulated material damage in both steel and concrete is further discussed in this research work. The numerical accuracy of the proposed method is validated by comparing the numerical results with the experimental data of two beam-column frame joints, a shear wall and a three-storey three-bay RC frame. According to the experimental setups, the RC joint and the shear wall specimens were tested under ultimate limit state cyclic loading, whereas the RC frame was tested under dynamic loading conditions. Based on the numerical findings, the proposed algorithm manages to capture the experimental results in an accurate manner and the numerical response of the understudy algorithmic implementation was found to exhibit computational robustness and efficiency.
Keywords: Nonlinear dynamic analysis; Concrete material modeling; Finite Element Method; Damage factor; Accumulated material damage